2022
DOI: 10.1111/jar.12989
|View full text |Cite
|
Sign up to set email alerts
|

Positive behavioural support for children and young people with developmental disabilities in special education settings: A systematic review

Abstract: Background: Positive behavioural support (PBS) can be effective in supporting children and young people (CYP) with developmental disabilities. This systematic review focused on describing the components and nine characteristics of PBS that have been used with CYP with developmental disabilities in special education settings, and the evidence for PBS effectiveness in these settings. Additionally, facilitators and barriers to PBS implementation, and experiences of stakeholders, were investigated. Method: Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The final domain (i.e., other sources of bias) is rated as either low or high risk. The SCED RoB has been used in a number of SCED systematic reviews to date (Beqiraj et al, 2022;Chawner et al, 2019;Germansky et al, 2020), providing additional insight into the validity of conclusions drawn from reviewed studies (see Tables 1 and 2).…”
Section: Risk Of Bias Toolmentioning
confidence: 99%
“…The final domain (i.e., other sources of bias) is rated as either low or high risk. The SCED RoB has been used in a number of SCED systematic reviews to date (Beqiraj et al, 2022;Chawner et al, 2019;Germansky et al, 2020), providing additional insight into the validity of conclusions drawn from reviewed studies (see Tables 1 and 2).…”
Section: Risk Of Bias Toolmentioning
confidence: 99%
“…With a few exceptions, experience of PBS within UK schools has focused on interventions used to address the behaviours that challenge specific pupils (Jackson Brown et al., 2014), and in many cases, these interventions have been conducted in special school settings (Paris et al., 2019). A recent international systematic review of PBS in special education contexts identified significant decreases in behaviours that challenge and increases in alternative behaviours, if increasing alternative behaviours was part of the interventions, across all PBS intervention research (Beqiraj et al., 2022). Increasingly, schools with some experience of PBS are beginning to look at academic and behavioural interventions across the whole school setting, adopting key elements of the SW‐PBS model adapted to their own environments.…”
Section: Introductionmentioning
confidence: 99%